A Pituitary Carcinoma Patient With Cerebrospinal Fluid Dissemination Showing a Good Response to Temozolomide Combined With Whole-Brain and Spinal Cord Radiotherapy: A Case Report and Literature Review - Du, Peng; Wu, Xuefan; Lv, Kun; Xiong, Ji; Geng, Daoying (Frontiers in Oncology, 2022)
Pituitary carcinoma (PC) is extremely rare, with its incidence only accounting for 0.1%-0.2% of pituitary tumor (PT). Existing histological features, including invasiveness, cellular pleomorphism, nuclear atypia, mitosis, necrosis, etc., can be observed in pituitary adenoma (PA), invasive PA (IPA) and PC. Invasion is not the basis for the diagnosis of PC. The diagnosis of PC is often determined after the metastases are found, hence early diagnosis is extraordinarily difficult. Owing to the conventional treatment for PC may not be effective, a large portion of patients survived less than one year after diagnosis. Therefore, it is of great significance to find an efficacious treatment for PC. We report a rare case of sparsely granulated somatotroph carcinoma with cerebrospinal fluid dissemination showing a favorable treatment response to temozolomide (TMZ) combined with whole-brain and spinal cord radiotherapy.